2022
DOI: 10.1038/s41598-021-04670-1
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation profile of human COVID-19 convalescent plasma

Abstract: Convalescent plasma is used to treat COVID-19. There are theoretical concerns about the impact of pro-coagulant factors in convalescent plasma on the coagulation cascade particularly among patients with severe COVID-19. The aim of this study was to evaluate the coagulation profile of COVID-19 convalescent plasma. Clotting times and coagulation factor assays were compared between fresh frozen plasma, COVID-19 convalescent plasma, and pathogen-reduced COVID-19 convalescent plasma. Measurements included prothromb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…These results are in agreement with a recent study showing no differences in CTs and coagulation factor assays, except for protein C antigen between CCP from adults who had recovered from COVID-19 and standard FFP from healthy adult volunteers. 38 Some variations in hemostasis between FFP, FDP, and the healthy control could be due to plasma sources and preparations (pooled FFP versus freshly prepared plasma from a healthy volunteer), 39 storage time, and condition. 40 Frozen storage time could affect the coagulation tests and factor activities of plasma even at À80°C.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in agreement with a recent study showing no differences in CTs and coagulation factor assays, except for protein C antigen between CCP from adults who had recovered from COVID-19 and standard FFP from healthy adult volunteers. 38 Some variations in hemostasis between FFP, FDP, and the healthy control could be due to plasma sources and preparations (pooled FFP versus freshly prepared plasma from a healthy volunteer), 39 storage time, and condition. 40 Frozen storage time could affect the coagulation tests and factor activities of plasma even at À80°C.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, these reports concluded that it is unlikely that this decrease has any clinical impact. By contrast, Klompas and colleagues recently demonstrated that the loss of coagulation factor activity in pathogen-reduced COVID-19 convalescent plasma had a clinical impact associated with the pathogen reduction process ( Klompas et al, 2022 ). Moreover, in agreement with our results, they demonstrated an increase in APTT and TT, suggesting that a slight prolongation of coagulation times may occur due to the combined loss of activity of several coagulation factors ( Hornsey et al, 2009 ; Klompas et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, Klompas and colleagues recently demonstrated that the loss of coagulation factor activity in pathogen-reduced COVID-19 convalescent plasma had a clinical impact associated with the pathogen reduction process ( Klompas et al, 2022 ). Moreover, in agreement with our results, they demonstrated an increase in APTT and TT, suggesting that a slight prolongation of coagulation times may occur due to the combined loss of activity of several coagulation factors ( Hornsey et al, 2009 ; Klompas et al, 2022 ). In line with these studies, we also found a significant reduction of functional protein C and FV, FX, and FXI levels, and a slight decrease in FVIII, FXIII and fibrinogen after inactivation.…”
Section: Discussionmentioning
confidence: 99%
“…76 Convalescent plasma treatment could be the solution for restoring the coagulation factor. 77 In a study conducted by Klompas et al 78 , low rates of thrombotic and thromboembolic events were found in COVID-19 patients, even in critically ill COVID-19 patients, who had convalescent plasma transfusion. 78 Convalescent plasma provides procoagulant and antifibrinolytic factors that could restore the endothelium glycocalyx and prevent vascular leakage.…”
Section: Restoration Of Coagulation Factormentioning
confidence: 97%
“…77 In a study conducted by Klompas et al 78 , low rates of thrombotic and thromboembolic events were found in COVID-19 patients, even in critically ill COVID-19 patients, who had convalescent plasma transfusion. 78 Convalescent plasma provides procoagulant and antifibrinolytic factors that could restore the endothelium glycocalyx and prevent vascular leakage. 77 Steric hindrance between receptor and ligand that provides by plasma and proteins in plasma have important role in fixing the endothelium glycocalyx.…”
Section: Restoration Of Coagulation Factormentioning
confidence: 97%